EVALUATION OF THE COAXIALITY OF OPTICAL SYSTEMS WITH LARGE MAGNIFICATION ON BLOCK CAMERAS - Tuan (Journal of Military Science and Technology, 2021)
The general tendency of observation weapons is the combination of sensors in one device, allowing multispectral observation devices. This facilitates flexible observation in different space, time and climate conditions. This type of observation devices is often called multispectral observation devices, which can be compact (hand-held) or an observation system. Multispectral observation devices often consist of a daylight channel, a night channel using thermal imaging technology or low light image intensifier systems in combanation with a laser rangefinder module. In this article, the authors suggested a method for surveillance, assessment and application of block cameras with the purpose of manufacturing multispectral observation systems and devices.